Electrical Generation System Small Size 50 Watts with Compressed Air Power - พลาศัย วสันต์; ปิยา อิบรอเฮ็ง (Princess of Naradhiwas University Journal, 2018)
This study is to investigate the 50 watt power generation with the principle of accumulating energy from compressed air with multiple wind turbines and compressed air at low wind speed to determine the generator speed. From the pressure inside the compressed air cylinder to find the relationship between the pressure, speed and capacity 50 watts. In experiment, a small 50 watt power system consists with (1) Pressure Transmitter to record the pressure inside the air tank. (2) Air Flow Transmitter to check the flow inside the pipe (3) Digital Tachometer to measure the wind speed of the generator (4) Data Logger to record each time period. Results from the maximum power by the pressure in the tank at 4 bars, 50 watts and a speed of around 940 rpm. This experiment was conducted. The pressure inside the tank after compressed air from the wind turbine started at 1.5 bar. Accumulates energy in compressed air cylinders and ends at 4 bars at an initial speed of 150 rpm, 5 watts of power and a maximum speed of 940 rpm. It has a 50 watts capacity. This experiment can continuously expand the power output by adding larger compressed air cylinders.